Asuhan Keperawatan Pada An. I Dengan Dengue Haemorrhagic Fever Di Ruang Mawar RSUD Banyudono - Giyatmi, Tri, Indrawati S. Kep, Ns., M.Si.Med (2015)
NURSING CARE TO An.I WITH DENGUE HEMORRHAGIC FEVER IN THE MAWAR ROOM OF RSUD BANYUDONO (Tri Giyatmi, 2015, 58 pages) ABSTRACT Background: Dengue hemorrhagic Fever is an infection disease caused by dengue virus, infected by Aides aegypty widespread in the tropics and sub-tropics. Dengue virus infection causes high mortality and morbidity worldwide. Purpose: To implement the nursing in clients with dengue hemorrhagic fever includes assessment, intervention, implementation and evaluation of nursing. Results: diagnoses that appear in the case as lack of fluid volume associated with displacement and intravascular to extravascular fluid, intake is not adequate, acute pain associated with the course of the disease, nutritional imbalances of the needs of the body associated intake is inadequate, nausea, vomiting, bleeding risks associated decrease in the number of platelets (thrombocytopenia). After the act of nursing for 3x24 hours showed lack of fluid volume is resolved in part, overcome pain, nutritional imbalance resolved, and resolved most of the risk of bleeding. Conclusion: The application of nursing care in accordance with the nursing process will achieve good results according with predetermined outcomes. to achieve the success of nursing care required cooperation between health team and the patient or family. Keywords: Dengue hemorrhagic fever, fluid balance, nursing care.